Quantitative longitudinal investigation of non-alcoholic steatohepatitis in mice by photoacoustic microscopy - Jianshuang Wei; Ren Zhang; Mingchen Jiang; Lulu Gao; Ximiao Yu; XiuLi Liu; Yanfeng Dai; Qingming Luo; Zhihong Zhang; Xiaoquan Yang (Photoacoustics)
Non-alcoholic steatohepatitis (NASH) is a prevalent chronic liver disease characterized by significant alterations in liver microvascular structures, leading to microcirculatory dysfunction and potentially contributing to various extrahepatic complications. In this study, we propose a longitudinal investigative pipeline based on liver photoacoustic microscopy (LPAM), integrating optical-resolution photoacoustic microscopy (OR-PAM), a modular liver window (MLW), a custom 3D-printed liver imaging mount (LIM), and a dedicated vessel-sinusoid separation and analysis method. This pipeline enabled continuous monitoring and quantitative assessment of microvascular changes in a NASH mouse model over a six-week period. As NASH progressed, vessel density decreased by 64.18 %, and hepatic sinusoid vessel coverage was reduced by 77.38 %. Furthermore, hepatic sinusoidal volume, length, radius, tortuosity, and density declined by 87.29 %, 83.92 %, 21.86 %, 71.57 %, and 86.81 %, Analysis of hepatic sinusoidal branches revealed a 51.80 % decrease in the fractal dimension of composite branches and a 54.90 % increase in that of dead-end branches. These findings suggest that lipid accumulation and inflammatory responses contribute to the progressive deterioration of hepatic microvascular structures, thereby exacerbating vascular damage. LPAM offers a high-resolution, label-free imaging approach for dynamic monitoring of NASH-associated microvascular alterations. This study advances our understanding of hepatic microcirculatory changes in NASH and provides valuable insights for both basic research and clinical management.